A new record of Abutilon grandifolium (subfamily Malvoideae, Malvaceae) from Qena Governorate, Egypt - Badry, Mohamed Owis; Tate, Jennifer A.; Sheded, Mohamed Gabr (Phytotaxa, 2018)
Abutilon grandifolium is reported for the first time for the flora of Egypt. The paper includes a comprehensive description, occurrence, comparison with closely related species, comments on habitat, and an updated identification key to the species of Abutilon in Egypt. In addition, photographs are given for easy identiﬁcation.